Leading Leadership Role in Promoting Career Immersion: An Analytical Study of The Opinions of a Sample of Teaching Staff in Technical Colleges at Sulaimaniyah Technical University - Tofik, Shilan Abdullah; Mohammed, Jalal Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The current study aims to know the role of entrepreneurial leadership with its dimensions (creativity, risk-taking, proactive, independence, offensive competitiveness) on job Involvement with its dimensions (emotional involvement, cognitive involvement, physical involvement), the study community represents the Technical colleges at Sulaimani Polytechnic University, and to reach this objective the researchers relied on reviewing studies and scientific sources to determine the dimensions of the study variables and establish their hypotheses, and for the practical side, the questionnaire form was prepared from (40) paragraphs on a sample of teaching staff consisting of (236) teaching staff within five colleges through the distribution of the questionnaire form electronically on the official website of the university, as well as distributing (62) forms manually. The forms evaluated before distributing by a group of arbitrators, and after distribution using the Statistical Package for Social Sciences (SPSS-25) program for analyzing data, the study reached a set of finding, the most important of it which is that the more the responding college councils adopt the entrepreneurial leadership style, the more that contributes to improving the levels of employee engagement in individuals, and the study offered a set of suggestions. to focus on providing requirements of entrepreneurial leadership dimensions.